IDENTIFICATION OF INTROGRESSIVE WINTER WHEAT LINES WITH WILD RELATIVES PARTICIPATION BY RUST RESISTANCE GENES - Rsaliev Aralbek,; Abugalieva Aigul,; Kozhakhmetov Kenebay,; Savin Timur Vladimirovich,; Rsymbetov Askhat,; Morgounov Alexey, (Scientific Journal of Pedagogy and Economics, 2020)
The genetic basis of winter wheat synthetic lines for leaf rust resistance was characterized by using molecular approaches. Molecular screening showed the presence of the Lr10 resistance gene for 24 lines (as Bezostaya 1 cvs and hybrids with it), for 4 samples-Lr13 (Zhetysu cvs and lines with participation), for 3 samples Lr16 (Karlygash cvs and lines with its participation), in 8 samples - Lr39 (Lr41) with Ae.cylindrica in the pedigree in combination with becrossing of cvs Erythrospermum 350 and cvs Steklovidnaya 24 and for 1 sample - Lr62, respectively. For 8 lines with high and partial resistance, Lr10 genes in combination with Lr39 (Lr41) and one sample with a combination of Lr10 + Lr16 genes were identified. The obtained result are consistent with the pedigree, according to which donors with these genes were used to create the studied lines. This material is a valuable source for the wheat breeding for resistance to leaf rust, identified genetically.